HR-LCMS assisted phytochemical screening of antioxidant, antibacterial activity of Priva cordifolia (L.f) Druce plant and molecular docking approach - N.B. Krishnamurthy; A.P. Ananda; H.S. Nagendra Prasad; P. Prabhuprasad; N. Manju; C.S. Karthik; H.S. Jayanth; T.V. Logaraj; K.R. Savitha (Results in Chemistry, 2023)
Ethnomedicinal plants have been employed for treatments in phytotherapy due to the quality, effectiveness, and assurance of herbal therapy. The present study aims to assess the different extracts (16 extracts) obtained from foliage, stem bark, root, and seeds by increased polarity solvent-based on extraction and analyze the antioxidant properties of Priva cordifolia (L.f) Druce plant. Total polyphenols and flavonoids have been found to range from 20.60 ± 0.19–148.20 ± 1.52 mg/g as gallic acid equivalent (GAE) and 7.31 ± 0.09–350.46 ± 12.80 mg/g as rutin equivalent (RE) respectively. All the extracts have been assessed for DPPH, ABTS scavenging radical and FRAP activity. Among these, methanol and acetone extract of the foliage showed excellent activity. The foliage extract was further fractioned and examined for antioxidant and antibacterial activity. A total of 27 metabolites were identified with the help of HRLC-MS. All the identified metabolites were tested for pharmacophore model, ADME, Blood-Brain Barrier, and Molecular docking analysis. In this insilico method, all compounds have given a good docking score and binding energy to the particular protein target, which ranges from − 6 to −10 against DNA gyrase protein (3G7B).The fraction was further evaluated for their cytotoxicity against normal cell L6 and revealed data showing insignificant toxicity. The foliage methanolic extract indicated a broad phytochemical in P. cordifolia and is yet to explore unknown vital constituents for the medicinal applications in the future.